Revocation of Norm Law No 11 Of 2006 about Aceh Government - Muhammad Rusjana; Muhammad Ridwansyah (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
The presence of the Election Law became a new breakthrough for the specificity of Aceh, because Article 571 letter d revoked Article 60 of the UUPA. Of course this was a very serious problem because the 1945 Constitution regulated special regions and there was even special recognition of areas that were considered special and special. This is recorded in Article 18B paragraph (1) of the 1945 Constitution which states that "the state recognizes and respects special and special regional government units regulated by law". The UUPA is the incarnation of the constitution but on the other Election Law revokes immediately without consideration of the DPRA, this is certainly a legal juridical because the UUPA requires that every amended article must pass the door to "consideration of DPRA".